Analisis Deskriptif dengan Kombinasi AI (Artificial Intelligence) Tentang Penggunaan Obat pada Pasien Penyakit Degeneratif di Puskesmas Tirtajaya Tahun 2025 - Dwi Wulan Apriani; Tio Widia Astuti Marpaung; Adelina Sisilia; Lenny Andika; Ayin Ayin (Jurnal Kridatama Sains dan Teknologi, 2026)
Degenerative diseases such as hypertension, type 2 diabetes mellitus (DM), stroke, and osteoarthritis are non-communicable diseases whose prevalence continues to rise along with increasing life expectancy and lifestyle changes, and these conditions frequently occur in combination within the same patient. Appropriate drug use is an important indicator of pharmaceutical service quality at primary health care facilities. This study aimed to analyze the pattern of drug use and evaluate its rationality among patients with combined degenerative diseases at Tirtajaya Public Health Center throughout 2025, incorporating artificial intelligence (AI) as a supporting tool for descriptive analysis, data categorization, and literature synthesis. This was a descriptive observational study with retrospective data collection using secondary data on visits, diagnoses, treatments, and laboratory results from 1 January to 31 December 2025. Of 408 patients diagnosed with degenerative disease, 102 patients met the inclusion criteria. Type 2 DM was the most common condition (51.0%), followed by osteoarthritis (31.4%), hypertension (15.7%), and stroke (7.8%). Most patients were female (68.6%) and aged 45-54 years (34.3%), with 90.2% having comorbidities, mainly secondary hypertension and dyslipidemia. Rationality evaluation of 291 prescription items for degenerative disease therapy showed 56.7% correct indication, 91.4% correct drug selection, 90.0% correct patient, and 93.5% correct dosage. Indication inaccuracies were mostly attributable to incomplete recording of comorbid diagnoses, while the use of oral corticosteroids for chronic osteoarthritis was identified as a deviation from Pionas standards. This study concludes that drug use among patients with combined degenerative diseases at Tirtajaya Public Health Center is generally rational, although completeness of diagnosis documentation and monitoring of high-risk groups still need improvement, and AI-assisted approaches may support the efficiency of similar descriptive analyses in the future